Corrigendum to "Sensitivity of Cuscuta species and their hosts to Anethum graveolens essential oil" - Sarić-Krsmanović, Marija; Gajić Umiljendić, Jelena; Radivojević, Ljiljana; Šantrić, Ljiljana; Đorđević, Tijana; Đurović-Pejčev, Rada (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2023)
nema